Relationship between intracranial pressure and phase-contrast cine MRI-derived measures of cerebrospinal fluid parameters in communicating hydrocephalus - Long, J.; Lin, H.; Cao, G.; Wang, M.Z.; Huang, X.J.; Xia, J.; Sun, Zhonghua (AME Publishing Company, 2019)
Background: To explore the correlation between intracranial pressure (ICP) and cerebrospinal fluid (CSF) parameters assessed by phase-contrast cine MRI (PC-MRI). Methods: Fifteen normal people and 80 subjects with communicating hydrocephalus who underwent PCMRI examinations from a single center were included in this cross-sectional study. In addition to recording patient’s age, heart rate, blood pressure and body mass index (BMI), ICP and CSF hemodynamic parameters, such as flow velocity and aqueduct diameter, were measured for correlation analysis. Results: The mean ICP and CSF aqueduct diameter in hydrocephalus patients were 151.05 mmH2O and 2.877 mm, respectively, and the maximum (6.938 cm/s) and mean (0.845 cm/s) CSF flow velocities were significantly higher in these patients compared with the controls (P<0.05). After adjusting for age, heart rate, blood pressure, and BMI, there was no significant relationship between peak velocity and ICP (P>0.05). Furthermore, a nonlinear relationship was observed between the ICP and the average velocity of CSF, and the ICP and aqueduct diameter. The ICP increased with the average velocity above 1.628 cm/s (P≤0.01), and the aqueduct diameter increased more than 3.6 mm (P<0.001). Conclusions: This study found significant correlations between ICP and average velocity and aqueduct diameter. These findings can be useful in assisting clinicians in predicting ICP more effectively, thus improving patient management.